On limit theorems of Fortet–Kac type - Kryžienė, Birutė; Misevičius, Gintautas (Lietuvos matematikos rinkinys, 2008)
We get the theorem of large deviations for sums of type f(T jt) satisfying the conditions weaker than in [5] (see [5, pp. 221–227]).